T-cell receptor–HLA-DRB1 associations suggest specific antigens in pulmonary sarcoidosis. Issue 3 (19th November 2015) - Grunewald, Johan; Kaiser, Ylva; Ostadkarampour, Mahyar; Rivera, Natalia V.; Vezzi, Francesco; Lötstedt, Britta; Olsen, Remi-André; Sylwan, Lina; Lundin, Sverker; Käller, Max; Sandalova, Tatiana; Ahlgren, Kerstin M.; et al.
In pulmonary sarcoidosis, CD4 + T-cells expressing T-cell receptor Vα2.3 accumulate in the lungs of HLA-DRB1*03 + patients. To investigate T-cell receptor-HLA-DRB1*03 interactions underlying recognition of hitherto unknown antigens, we performed detailed analyses of T-cell receptor expression on bronchoalveolar lavage fluid CD4 + T-cells from sarcoidosis patients. Pulmonary sarcoidosis patients (n=43) underwent bronchoscopy with bronchoalveolar lavage. T-cell receptor α and β chains of CD4 + T-cells were analysed by flow cytometry, DNA-sequenced, and three-dimensional molecular models of T-cell receptor-HLA-DRB1*03 complexes generated. Simultaneous expression of Vα2.3 with the Vβ22 chain was identified in the lungs of all HLA-DRB1*03 + patients. Accumulated Vα2.3/Vβ22-expressing T-cells were highly clonal, with identical or near-identical Vα2.3 chain sequences and inter-patient similarities in Vβ22 chain amino acid distribution. Molecular modelling revealed specific T-cell receptor-HLA-DRB1*03-peptide interactions, with a previously identified, sarcoidosis-associated vimentin peptide, (Vim)429–443 DSLPLVDTHSKRTLL, matching both the HLA peptide-binding cleft and distinct T-cell receptor features perfectly. We demonstrate, for the first time, the accumulation of large clonal populations of specific Vα2.3/Vβ22 T-cell receptor-expressing CD4 + T-cells in the lungs of HLA-DRB1*03 + sarcoidosis patients. Several distinct contact points between Vα2.3/Vβ22 receptors and HLA-DRB1*03 molecules suggest presentation of prototypic vimentin-derived peptides. Clonal CD4 + lung T-cells associating with HLA-DRB1*03 molecules indicate specific antigens in pulmonary sarcoidosis http://ow.ly/UB81x